Extent of Home Delivery among Women Who Gave Birth in the Last One Year in Serbo, Kersa Woreda, Jimma Zone, Oromia Region, Southwest Ethiopia - Gemechu Terefe; Ahmedin Teha; Tujuba Diribsa; Daba Abdisa (Hindawi Limited, 2022)
Background. Home delivery is childbirth in a nonclinical setting that takes place in a residence rather than in a health institution. Maternal morbidity and mortality are global health challenges, and developing countries contribute to most of the maternal deaths. Objective. This study aimed to assess the extent and associated factors for home delivery in Serbo, Kersa Woreda, Jimma Zone, Southwest Ethiopia. Method. A community-based cross-sectional study was employed among the 240 study participants. Data were collected by using systematic sampling technique from July 5 to 26, 2021, via a pretested semistructured questionnaire through face-to-face interview, and analyzed by a statistical package for the social sciences version 23.0. Bivariable and multivariable logistic regression analyses were carried out to identify factors associated with the extent of home delivery, and factors associated with the extent of home delivery were declared at a p value <0.05. ResultIn this study, the extent of home delivery was 28.7%. Identified factors statically associated with home delivery were low monthly income (AOR = 16.7, 95% CI: (2.028-13,83)), only the husband as the decision-maker (AOR = 5.0, 95% CI: (1.252-20.021)), never had a history of ANC follow-up (AOR = 5.7, 95% CI: (2.358-16.3)), poor knowledge toward delivery service (AOR = 3.0, 95% CI: (1.661-5.393)), negative attitude toward delivery service (AOR = 2.2, 95% CI: (1.054-4.409)), and large family size (AOR = 2.2, 95% CI: (1.187-4,119)). Conclusion. When compared to the Ethiopian Demographic and Health Survey 2016, the prevalence of home delivery among women who gave birth in the last one year was low in this study. The study participants' identified factors that were significantly linked with home delivery were low monthly income, only husband as decision maker, no ANC follow-up, poor knowledge of delivery services, negative attitude toward delivery services, and large family size. Health professionals and health extension workers should raise awareness about institutional delivery and birth readiness so that women can give birth at a health facility even if labor begins unexpectedly.